DEVELOPMENT AND IMPLEMENTATION PROBLEMS OF SCIENTIFIC AND TECHNOLOGICAL PROGRESS STRATEGIC PROGRAMS IN THE RUSSIAN FEDERATION REGIONS: SOCIAL AND ORGANIZATIONAL BARRIERS (based on the remote study in 14 regions of the country with different levels of socio-cultural modernization) - A. V. Tikhonov; V. S. Bogdanov; A. A. Merzlyakov; K. E. Guseinova (Модернизация, инновация, развитие)
Purpose: substantiation of sociological research problems associated with the socio-organizational barriers appearance in the implementation of scientific and technological development Strategies (SSTD) in regions with different levels of socio-cultural modernization and their readiness assessment to innovate according to innovation and technological systems criteria and elements.Methods: research methodology is the principles of logical and mathematical justification of obtaining new knowledge: from the formulation of a practically significant problem to the empirical interpretation of the used concepts and the new result. The elements of the research program are the problem, object, subject, hypotheses, goals and tasks, and the methodological method is to use of empirical scales to test hypotheses and substantiate the results. The main method of collecting primary data is to obtain them remotely from the selected regionsoficial websites.Results: to get the proof of the possibilities of more full use of the feedback potential in the regional management systems in the development of Strategic documents and their implementation. It is shown that the main reason for the appearance of socio-organizational barriers is that the interests of central industries and departments today consistently prevail over the of spatial development regions interests with different levels of socio-cultural modernization.Conclusions and relevance: sociological support Opportunities of Strategic documents preparation and implementation gives a preliminary, but still convincing picture of this process organization. It can be taken by central and local authorities in Strategic documents next stages.